The History of Knowledge Development in East (Islam) and West - Muhammad Ediyani (Cyber Media Indonesia, 2022)
This article aims to find out the history of the development of science from time to time recorded by existing historical literature and mentions some of the figures behind the discovery of scientific theories and their development. The phases of the development of science are called periodization in the history of the development of science starting from ancient times, middle ages, modern times and contemporary times. While the phases of the development of science in the Islamic world began from the time of the Prophet, Khulafau Ar-Rashidin, the Umayyads, Daula Abbasids and the revival of Islam until now. When science in the European world suffered a setback but on the contrary what happened in the Islamic world of science developed rapidly until the peak of glory.